1997
DOI: 10.1080/10683169608409792
|View full text |Cite
|
Sign up to set email alerts
|

British and nigerian adolescents' lay theories of youth crime

Abstract: Thisrtud~eumined~orrculturaldi&rencsr in cxpluutionr for the c a m of youtb quatiom were d y r s d wing an attribution theory frmcwork. British children tended to we personal nplrnrtionr of youth aime (75%), in oompuiron, N~~u~u I childnn tended to UIC ntuatid cxpluutionr of youth aimC (61%). Tbm w u a nide Wiety of rapollla within b a e broad categories, the most frequently occunhg verbatim rapona for British 12-yar olda were "for fun" (19.2%) and "baause they M bored" (ZaO%) for the British 14-yar 016. For N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
4
12
1
1
Order By: Relevance
“…Brown & Lalljee (1981) found that adolescents tended to explain crimes in terms of personal causes rather than situational causes. Cultural differences in British and Nigerian adolescents' explanations for youth crime were found by Pfeffer et al (1996). They found that British adolescents tended to use internal attributions and that Nigerian adolescents tended to use external attributions.…”
Section: Social Transformation Theoriesmentioning
confidence: 90%
See 2 more Smart Citations
“…Brown & Lalljee (1981) found that adolescents tended to explain crimes in terms of personal causes rather than situational causes. Cultural differences in British and Nigerian adolescents' explanations for youth crime were found by Pfeffer et al (1996). They found that British adolescents tended to use internal attributions and that Nigerian adolescents tended to use external attributions.…”
Section: Social Transformation Theoriesmentioning
confidence: 90%
“…A basic distinction within attribution theory is between internal and external causes of behavior. Social psychologists (Smith & Bond, 1994;Pfeffer et al, 1996) have consistently reported that in Western cultures over-emphasis is placed on internal attributions, whereas in non-Western cultures there is evidence that more emphasis is placed on external attributions (Weisz et al, 1984). This difference is thought to be due to a focus on the individual and personal responsibility in Western societies and on the family and collective responsibility in non-Western societies (Pfeffer et al, 1996).…”
Section: Attribution Theorymentioning
confidence: 92%
See 1 more Smart Citation
“…However, although Pfeffer et al (1997) obtained data about what children attributed to other children's criminal behaviour, no study has been conducted that allowed African children to account for their own offending. It has been argued that there is an over-emphasis on internal attributions in western societies (Moghaddam et al, 1993).…”
Section: Reasons For Offendingmentioning
confidence: 99%
“…However, in the field of social psychology, a few studies have been conducted. Pfeffer et al (1997) conducted a cross-cultural study of 196 British and Nigerian adolescents' explanations for the causes of youth crime using an attributions-theory framework; they found that British adolescents tended to blame the individual for youth crime. In contrast, Nigerian adolescents tended to blame 'other persons' and environmental factors for youth crime.…”
Section: Reasons For Offendingmentioning
confidence: 99%